2019
DOI: 10.1155/2019/3061607
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antioxidant Potential with Coenzyme Q10 Suppressed Invasion of Temozolomide-Resistant Rat Glioma In Vitro and In Vivo

Abstract: The main reasons for the inefficiency of standard glioblastoma (GBM) therapy are the occurrence of chemoresistance and the invasion of GBM cells into surrounding brain tissues. New therapeutic approaches obstructing these processes may provide substantial survival improvements. The purpose of this study was to assess the potential of lipophilic antioxidant coenzyme Q10 (CoQ10) as a scavenger of reactive oxygen species (ROS) to increase sensitivity to temozolomide (TMZ) and suppress glioma cell invasion. To tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 51 publications
0
46
1
Order By: Relevance
“…Of the 327 articles identified in Scopus, after screening, 48 articles were excluded (18 reviews, 15 conference papers, 8 book chapter/series, 2 notes, 2 publications in other languages, 1 conference review, 1 editorial, and 1 short survey), and 260 articles were excluded after eligibility analysis (120 articles did not report the therapeutic approach used for glioblastoma on-a-chip, 110 articles reported only the usage of the microfluidic device for analysis of part of the experiment, such as CHIP-Seq, CHIP-qPCR, and chromatin immunoprecipitation—CHIP, and 30 articles developed the study in silico), thus, only 19 articles were included from this database. As shown in Figure 1 , only 22 unduplicated full-text articles were included in this review [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], and the histogram and spider chart show the distribution of articles by year and research centers, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 327 articles identified in Scopus, after screening, 48 articles were excluded (18 reviews, 15 conference papers, 8 book chapter/series, 2 notes, 2 publications in other languages, 1 conference review, 1 editorial, and 1 short survey), and 260 articles were excluded after eligibility analysis (120 articles did not report the therapeutic approach used for glioblastoma on-a-chip, 110 articles reported only the usage of the microfluidic device for analysis of part of the experiment, such as CHIP-Seq, CHIP-qPCR, and chromatin immunoprecipitation—CHIP, and 30 articles developed the study in silico), thus, only 19 articles were included from this database. As shown in Figure 1 , only 22 unduplicated full-text articles were included in this review [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], and the histogram and spider chart show the distribution of articles by year and research centers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the selected studies used in this study, 91% produced in-house devices [ 39 , 40 , 41 , 42 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], only 9% of studies used commercial devices [ 43 , 47 ], due to the variability of device design used in the research. Regarding technology used in this fabrication, different lithographic techniques were used, namely, 68.2% soft lithography [ 39 , 40 , 42 , 43 , 46 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 58 , 59 , 60 ], 13.6% photolithography [ 51 , 56 , 57 ], and 4.5% two-photon lithography [ 41 ], 4.5% used 3D-printing systems [ 44 ], and 9.1% did not report the technology used [ 45 , 47 ]. The main material of the devices was 88% polymers (72% PDMS [ 39 , 40 , 42 , 43 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic-based 3D cultures could be also successfully used to evaluate the potential of different compounds to overcome MDR. As previously mentioned, Burić et al, recently reported the sensitization of resistant RC6 cells to temozolomide by its combining with coenzyme Q10 in a 3D microfluidic device with collagen hydrogel (Burić et al, 2019).…”
Section: Single and Multiple Drug Evaluation In Microfluidic-based 3d Culturesmentioning
confidence: 90%
“…Moreover, the deregulation of the cellular energetic mechanisms present in the TME can induce the production of reactive oxygen species (ROS). The oxidative state, modulated by the antioxidant coenzyme Q10, and its relation with the cell death and resistance mechanisms have been studied by Burić et al, in a glioblastoma model (Burić et al, 2019). A significant increase in temozolomide sensitivity upon combined treatment with coenzyme Q10 was observed in drug-resistant glioblastoma cells located in the highly oxygenated zone of the microfluidic chip when compared to the hypoxic area.…”
Section: Studying Changes In Cellular Metabolismmentioning
confidence: 99%
“…A low level of CoQ 10 in patients was positively correlated with poor prognosis [4][5][6]. Another study also suggested that CoQ 10 can inhibit malignant tumor cell invasion with its antioxidant capacity [7].…”
Section: Introductionmentioning
confidence: 99%